청소년의 건강행위 실천이 정신건강에 미치는 영향 - 윤현정; Hyun Jung Yun (보건정보통계학회지, 2022)
Objectives: The study aimed to investigate the effect of health behaviors practice on mental health in adolescents. Methods: Data from 16th (2020) Korea Youth Risk Behavior Web-based Survey were used. The study sample included 54,948 middle and high school students. The data were analyzed using Rao-Scott χ2, t-test, and complex samples logistic regression. Results: The prevalence of subjects with anxiety, depression, and suicidal ideation was 9.2%, 25.2%, and 10.9%, respectively. Health behaviors practice such as smoking, drinking, weight control, exercise, eating breakfast, sufficient sleep, and fruit intake were found to be significantly related to mental health. After controlling general characteristics, mental health factors such as anxiety, depression, and suicidal ideation were influenced by health behaviors practice. Conclusions: Interventions, including comprehensive health behaviors, should be strengthened to prevent mental health problems in adolescents.